(untitled) (Legal journal - Research in Legal and Social Sciences, 2022)
The recusal of prosecutors is a power granted by law to litigants in criminal proceedings, regulated by art. 57 -recusals and inhibitions- of the Code of Criminal Procedure. In this regard, Law No. 4685/12 amended the aforementioned article, which merits a study to facilitate its interpretation and application in the course of criminal proceedings. This work is aimed at the study of the meaning and scope of the grounds for recusal provided by law and the comparative analysis with the arguments used by the litigants to interpose them. In this context, it should be borne in mind that the Public Prosecutor’s Office is an essential party in the criminal proceeding, so that the filing of a challenge against its members affects the development of the proceeding in progress. For this reason, the approach to this institute is important for the criminal justice system. As for the method, the research is documentary, with a qualitative, non-experimental approach. The instrument used was the bibliographic record. In order to arrive at the results as techniques, the reading, comparison and analysis of national regulations in force, criminal and civil, referring to the subject were carried out. In addition, this paper includes a study of the resolutions of the Supreme Court of Justice and the Public Prosecutor’s Office regarding recusals of public prosecutors in 2021. The result is expected to contribute to the knowledge and better use of this institute, to ensure objective application in the exercise of its functions.